Plasmonic metal nanostructures as performance enhancers in emerging solar cells: A review - Abdul Subhan; Abdel-Hamid. I. Mourad (Next Materials)
Improvements in solar cell technology are crucial for effectively harnessing solar energy for a sustainable future. In the quest for developing cost-efficient and high-performance solar cells, various research groups have made strenuous efforts by employing novel techniques and absorber materials. Owing to their excellent optical and electronic properties, plasmonic metal nanostructures are highly sought-after materials in the scientific community among the various nanomaterials utilized for energy conversion applications, especially for solar cells. This review compares the current trends in implanting these stable metallic nanostructures within the solar cell architecture to improve the photon harvesting capability. The categories of emerging solar cells focused herein include perovskite, dye-sensitized, and quantum dots, investigating the role of size and morphology of metal nanoparticles in boosting power conversion efficiency. A special focus is given on the physics behind the light entrapment due to the localized surface plasmon resonance effect observed noble metal nanostructures resulting in hot electron generation and injection to boost the electrical performance in these emerging solar cells. This review also provides a comparative analysis of plasmonic approaches against other alternatives to enhance photocurrent in solar cells. Finally, discussion on the prospects of plasmonic nanomaterials for solar cell development alongside the challenges associated with achieving efficient solar cell fabrication are presented with a perspective.